Analisa Kepuasan Mahasiswa terhadap Kualitas Pelayanan Pendidikan - Ni Luh Anik Puspa Ningsih; Dewa Ayu Putu Niti Widari; I Made Artawan (Universitas Warmadewa, 2020)
Abstract-During the learning process, students have experience with educational services at the University. This experience will create a perspective on the quality of education services provided. This will be related to the level of student satisfaction. This level of satisfaction will made an opinions. That generally will quickly spread, to family, friends and society. Bad opinion will affect the University's image, so it is important to analyze student satisfaction. A survey are held to gain information about student satisfaction.. This research was conducted at Warmadewa University, a private university in Denpasar, Bali. Survey results are summarized in the index of student satisfaction with the quality of education services at Warmadewa University. Based on the dimensions of service quality, namely tangibles, reliability, empathy, responsiveness, assurance students feel